SABR 50 at 50 : The Society for American Baseball Research's Fifty Most Essential Contributions to the Game - Thorn, John, 1947-; Tan, Cecilia, 1967-; Pomrenke, Jacob; Heaphy, Leslie A., 1964-; Bush, Scott, 1982-; Armour, Mark L.; Nowlin, Bill, 1945- (Book collections on Project MUSE., 2020)
"SABR 50 at 50 celebrates and highlights the Society for American Baseball Research's wide-ranging contributions to the game of baseball"--